Pelaksanaan Perlindungan Hukum bagi Pemilik Hak Cipta Musik dan Lagu dalam Pembayaran Royalti oleh Yayasan Karya Cipta Indonesia - Ni Made Harini; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2021)
Copyright gives an exclusive title to the work of the author which is granted by law as an award. The copyright function protects creators from copyright infringement. This study aims to explain the form of legal protection for music and song copyright owners in royalty payments by the Indonesian copyright works foundation and to describe what factors influence royalty payments and dispute resolution efforts faced by music and song copyright holders in royalty payments by the Karya Foundation. Indonesian copyright. This type of research is an empirical legal research with a conceptual approach to legal issues of fact and sociology. The data sources used were primary and secondary legal materials. The results of the study indicated that copyright is regulated in Law Number 28 of 2014 concerning Copyright. The form of copyright law protection, namely legal protection of moral rights and legal protection of economic rights. Creators and the KCI Foundation have rights and obligations, in the process of paying royalties experiencing several obstacles and supporters experienced by the KCI Foundation creators and copyright users. Dispute settlement efforts through alternative arbitration and court dispute resolution.